Factitious illness: recognition and management. Issue 12 (December 1992) - Eminson, D M; Postlethwaite, R J
Abstract : An analysis of Munchausen syndrome by proxy is proposed, which involves a categorisation of parental behaviour in terms of desire to consult and ability to distinguish the child's needs from parents' own needs. The Munchausen syndrome by proxy case is proposed as one extreme of a much broader and commoner group for which the term factitious illness is used. An outline of assessment and investigation is given, applicable to all degrees of factitious illness, together with a model of collaboration between paediatrician and child psychiatrist. The role of the child psychiatrist is described. Collaboration results in a broader analysis of the situation which facilitates understanding and points the way to appropriate intervention.